A genre-specific study of English and Persian newspaper editorials / Alireza Bonyadi Babaee - Babaee, Alireza Bonyadi (2011)
Newspaper editorials constitute a part of media discourse, which is an extremely important field of research in intercultural rhetoric analysis. The interface between the linguistic analysis of newspaper editorials and teaching of English as a foreign/second language is also a relevant issue in language teaching. Thus, drawing on the theory of inter-cultural rhetoric analysis and considering the important role of newspaper editorials in shaping public opinions, the present study aimed at conducting a genre-specific analysis of newspaper editorials culled from the editorials of the English newspaper, The New York Times, and those of Persian newspaper, Tehran Times. Addressing different discourse strategies that newspaper editorials employ for propagating their preferred ideologies, the study specifically focused on the schematic analysis of the editorials and also the types of the rhetorical structures they employed for communicating their intended opinions. The findings of the study revealed that the editorials in the two papers were similar in having the same schematic structures and moves. However they were found to be different in terms of realizing the moves. Furthermore, the editorial writers in the two papers, throughout the headlines and the main texts, tried to influence their readers' understanding of the news events by employing certain textual and rhetorical devices. The study has also offered some pedagogical implications of the findings that might provide the ESL/EFL teachers and students with the required knowledge on the discourse conventions in a certain sub-genre namely newspaper editorials making them ready to use the newspaper editorials in the classrooms.